Evaluation of Group-Based Family Income Improvement Program Using Context, Input, Process, Product (CIPP) Evaluation Model - Reny Damayanti; Gustava Yandi; Riswan Yudhi Fahrianta; Zainal Arifin (International Journal of Multi Discipline Science, 2022)
This study aims to determine the implementation of the UPPKA program using the CIPP evaluation model. This research was evaluative research using a qualitative descriptive approach. Data collection techniques were carried out using observation, interviews, and documentation. Data analysis was done by reducing the data, presenting the data, and drawing conclusions. The triangulation used a source and method to compare the opinions of interested parties on a group-based family income increase program in Pulang Pisau Regency, Central Kalimantan Province. The results showed that (1) the context evaluation was not good, because there was no legal basis, namely the Regent's Regulation even though the implementation of the UPPKA program and training, the suitability of the needs analysis, the suitability of the background and the objectives of the UPPKA program were in accordance with the expected competencies; (2) evaluation of input was not good because the organizers in this case were related agencies that had not yet matured in the context of planning, even though the family planning instructor/instructor was competent and masters the material, UPPKA members were in accordance with the criteria and procedures, the facilities and infrastructure were supported; (3) the evaluation process was not good because the suitability of the activity schedule was uncertain, the performance of the organizers had not been maximized due to planning constraints that affect the implementation of activities even though the family planning instructor was optimal, UPPKA members were still passive, and the evaluation was carried out thoroughly, both evaluation of members, instructors/KB instructors and organizers, where only family planning instructors/extension workers work optimally. Product evaluation was not good because UPPKA members had not mastered the context of administration and management.